The Influence of Digital Marketing on Buying Interest, Purchase Decisions, and Consumer Satisfaction of Fashion Products in TikTok Shop - Ruswanti Mulyana; Siti Mujanah; Achmad Yanu Alif Fianto (Universitas KH. Abdul Chalim Mojokerto, 2026)
The development of digital technology has changed marketing methods from traditional methods to methods that use technology. This study aims to determine the influence of digital marketing on purchasing interest, purchasing decisions, and consumer satisfaction with fashion products on TikTok Shop. The method used is quantitative with an explanatory approach. Data were obtained from an online questionnaire given to 151 people who had purchased fashion products on TikTok Shop, then analyzed using SPSS with validity, reliability, correlation, and simple linear regression tests. The results showed that digital marketing has a positive and significant influence on purchasing interest (R² = 0.518), purchasing decisions (R² = 0.531), and consumer satisfaction (R² = 0.473). This means that the more effective the digital marketing strategy used, the higher the purchasing interest, purchasing decisions, and consumer satisfaction. This study provides a theoretical contribution to the development of digital marketing science, as well as providing practical recommendations for small and medium-sized business actors in the fashion sector on TikTok Shop to maximize digital marketing strategies as a way to increase sales and customer loyalty.